ASSESSMENT OF THE COMPRESSIVE STRENGTH O F CONCRETE BY THE SONREB TESTS : CASE OF THE POLE MOSQUE OF ORAN - Bousmaha, S; Cheikh-Zouaoui, M; Chergui, S (university of el oued/جامعة الوادي, 2021)
The non destructive evaluation of concrete is a vital part and an active and interesting field of research which can be a fundamental step in the process of heritageization of contemporary architecture, especially for the n e w large mosques in Algeria. Th e present study consists of the assessment of the concrete structure of the pole mosque of Oran by applying a protocol of non destructive testing of the compressive strength based on the combination of two tests of the SonReb approach; ultrasonic pulse vel ocity (UPV) and rebound index (RN). This method not only makes it possible to check the physical state of the structure, but also to collect the information necessary to predict the possibility of use in the future. The resul t s of the experimental tests ob tained indicate a very acceptable quality of the conc rete of the pole mosque of Oran
Article
Keywords: mosque, concrete, combination, compressive strength, SonReb